Maternal and foetal outcomes of deliveries attended to at Emkhuzweni Health Centre in Swaziland - Woreta, Fikadu (University of Limpopo (Medunsa Campus), 2010)
Abstract AIM The aim of the study was to measure the maternal and foetal outcomes of the deliveries attended to at Emkhuzweni Health Centre, Swaziland. Objectives The objectives of the study were: .:. To determine maternal outcomes of the deliveries attended to at Emkhuzweni Health Centre. .:. To determine foetal outcomes of the deliveries attended to at Emkhuzweni Health Centre. .:. To identify risk factors that affect maternal and foetal outcomes at Emkhuzweni Health Centre Methods A retrospective chart review was performed for all 520 deliveries at Emkhuzweni Health Centre between January 1,2007 and December 31 2007. Labouring mothers were eligible for the study if they met the inclusion criteria. The study was conducted after ethical approvals from the relevant authorities were obtained. Data were obtained from records for the following variables: age, address, gravidity, parity, health service where ANC was attended, risk factor, mode of delivery, maternal condition after delivery and post-delivery maternal hospital stay. For each foetus, the APGAR score at the first and fifth minute, weight and sex of the neonate and condition after delivery were recorded. Results The results revealed that the maternal outcomes after delivery were normal for 89.85% of the mothers; 3.4% of those who delivered at EHC had PPH, 5.4% developed puerperal sepsis, 1 % PIH and 0.2% cases resulted in maternal death. The majority of mothers (61.7%) were discharged from the maternity ward in less than 24 hrs. As far as foetal outcomes were concerned, normal babies accounted for 68% of births, early onset neonatal sepsis for 1.9%, congenital malformation (0.6%), stillbirth (1.5%), low birth weight (9.2%), preterm babies (17.8 %) and neonatal death (0.4%0. Conclusion This study found that the maternal outcomes at Emkhuzweni Health Centre in 2007 were similar to those in Swaziland as a whole and in other developing countries, except that there was a higher rate of pre-term delivery among pregnant women assisted at Emkhuzweni Health Centre. The foetal outcomes of Emkhuzweni Health Centre in 2007 were similar to the data from developing countries. Additionally, however; significant numbers of pre-term babies were delivered and a high incidence of neonatal sepsis was observed at the Health Centre. Some of the risk factors for the observed maternal and foetal outcomes were poor antenatal care attendance, distance of the Health Centre from the home state of the pregnant woman, preterm labour, under age and teenage pregnancies.
Thesis (M Med(Family Medicine)) -- University of Limpopo, 2010.
Keywords: Maternal health services; Foetal outcome